Aristotelian and Islamic Moral Philosophy: A Comparative Ethics - Acikgenc, Alparslan (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Aristotelian and Islamic Moral Philosophy: A Comparative Ethics